What Makes Cities More Competitive? Spatial Determinants of Entrepreneurship in India - Ghani, Ejaz; Kerr, William R.; O'Connell, Stephen D. (World Bank, Washington, DC, 2013)
Policy makers in both developed and developing countries want to make cities more competitive, attract entreprepreneurs, boost economic growth, and promote job creation. The authors examine the spatial location of entrepreneurs in India in manufacturing and services sectors, as well as in the formal and informal sectors, in 630 districts spread across 35 states/union territories. They quantify entrepreneurship as young firms that are less than three years old, and define entry measures through employment in these new establishments. They develop metrics that unite the incumbent industrial structures of districts with the extent to which industries interact through the traditional agglomeration channels. The two most consistent factors that predict overall entrepreneurship for a district are its education and the quality of local physical infrastructure. These patterns are true for manufacturing and services. These relationships are much stronger in India than those found for the United States. The authors also find strong evidence of agglomeration economies in India's manufacturing sector. This influence is through both traditional Marshallian economies like a suitable labor force and proximity to customers and through the Chinitz effect that emphasizes small suppliers. India's footprints in structural transformation, urbanization, and manufacturing sector are still at an early stage. At such an early point and with industrial structures not yet entrenched, local policies and traits can have profound and lasting impacts by shaping where industries plant their roots.